A Nomogram for Predicting Cancer-Specific Survival in Children With Wilms Tumor: A Study Based on SEER Database and External Validation in China - Tan, Xiaojun; Wang, Jinkui; Tang, Jie; Tian, Xiaomao; Jin, Liming; Li, Mujie; Zhang, Zhaoxia; He, Dawei (Frontiers in Public Health, 2022)
Background: Wilms tumour (W.T.) is the most common tumour in children. We aim to construct a nomogram to predict the cancer-specific survival (CSS) of Wilms tumours in children and externally validate in China. Methods: We downloaded the clinicopathological data of children with W.T. from 2004 to 2018 in the SEER database. At the same time, we used the clinicopathological data collected previously for all children with W.T. between 2013 and 2018 at Children's Hospital of Chongqing Medical University (Chongqing, China). We analyzed the difference in survival between the patients in the SEER database and our hospital. Cox regression analysis was used to screen for significant risk factors. Based on these factors, a nomogram was constructed to predict the CSS of children with W.T. Calibration curve, concordance index(C-index), the area under the receiver operating curve(AUC) and decision curve analysis (DCA) was used to evaluate the accuracy and reliability of the model. Results: We included 1045 children with W.T. in the SEER database. At the same time, we collected 112 children with W.T. in our hospital. The Kaplan-Meier curve suggested that children in China with W.T. had a higher mortality rate than in the United States. Cox regression analysis revealed that age, lymph node density (LND), and tumour stage were significant prognostic factors for the cases in the SEER database. However, the patients in our hospital only confirmed that the tumour stage and the number of positive regional lymph nodes were significant factors. The prediction model established by the SEER database had been validated internally and externally to prove that it had good accuracy and reliability. Conclusion: We have found a survival prognosis prediction model for children with W.T., which has been validated internally and externally to prove accuracy and reliability.